PATH ANALYSIS ORGANIZATIONAL COMMITMENT AND MICRO CULTURE AGAINST LEADERSHIP LECTURER IN HIGHER EDUCATION - Suryanto, Tulus; Rahmat, Abdul (AKADEMIKA: Jurnal Pemikiran Islam, 2018)
Abstract This study aims to examine organizational commitment and micro culture towards lecturer leadership. Population in this research is all lecturer at State University of Gorontalo, obtained by sampel counted 62 people by using random sampling technique. Data collection techniques used are, tests, questionnaires and documents. Data analysis technique used is inferential analysis. Test of normality of regression data, test of regression coefficient significance, linearity test of regression equation, and hypothesis test using path analysis. The results showed that: (1) there is a direct influence of organizational commitment from the calculation of coefficient value of path X1 to Y obtained value = 0.615. Based on the results of the calculation of the significance of the path coefficient obtained tcount = 8.023 and ttable = 2.001 at the level of significance a = 0.05 with degrees of freedom (db) = 59. Because the value of tcount = 8.023> ttable = 2,001 it is concluded that the coefficient of path X1 to Y is significant; (2) there is direct influence of campus micro culture from calculation of coefficient value of path X2 to Y obtained value = 0,363. Based on the results of the calculation of the significance of the path coefficient obtained tcount = 4.759 and ttable = 2.001 at the level of significance a = 0.05 with degrees of freedom (db) = 59. Because the value of tcount = 4.759> ttable = 2,001 it is concluded that the coefficient of path X2 to Y is significant; (3) there is direct influence of organizational commitment to micro culture from result of calculation of coefficient value of path X1 to X2 obtained value = 0,753. Based on the calculation of significance test the path coefficient obtained tcount = 8.852 and ttable = 2,000 at the level of significance a = 0.05 with degrees of freedom (db) = 60. Because the value of tcount = 8.852> ttable = 2,000 it is concluded that the coefficient of path X1 to X2 is significant. Thus, the lecturer's leadership can be improved through organizational commitment and campus micro culture so that lecturers continue to improve their performance. Keywords: Organizational Commitment, Micro Culture, and Leadership Abstrak Studi ini ditujukan untuk mengkaji komitmen organisasi dan budaya mikro terhadap kepemimpinan dosen. Populasi dari penelitian ini adalah semua dosen Universitas Negeri Gorontalo dengan sampel sebanyak 62 yang ditentukan secara acak. Data penelitian dikumpulkan melalui tes, kuesioner, dan dokumen. Data dianalisis secara inferensial menyakup tes normalitas regresi, tes signifkansi koefisien regresi, tes linearitas dan ekuasi regresi, dan analisis jalur untuk pengujian hipotesis. Hasil penelitian menunjukkan: (1) terdapat hubungan langsung antara komitmen organisasi berdasar perhitungan koefisien analisis jalur X1 terhadap Y dengan nilai 0,615. Hasil perhitungan signifikansi analisis jalur didapatkan t-hitung 8,023 dan t-tabel 2,001 pada tingkat signifikansi 0,05 dengan derajat kebebasan 59. Karena t-hitung > t-tabel, disimpulkan bahwa koefisiensi jalur X1 terhadap Y adalah signifikan; (2) terdapat hubungan langsung antara budaya mikro kampus berdasar perhitungan nilai koefisien jalur X2 terhadap Y sebesar 0,363. Hasil perhitungan signifikansi koefisien analisis jalur didapatkan t-hitung 4,759 dan t-tabel 2,001 pada tingkat signifikansi 0,05 dengan derajat kebebasan 59. Karena t-hitung > t-tabel, disimpulkan bahwa koefisiensi jalur X2 terhadap Y adalah signifikan; (3) terdapat hubungan langsung antara komitmen organisasi terhadap budaya mikro berdasar perhitungan nilai koefisien jalur X1 terhadap X2 sebesar 0,753. Hasil perhitungan signifikansi koefisien analisis jalur didapatkan t-hitung 8,852 dan t-tabel 2,000 pada tingkat signifikansi 0,05 dengan derajat kebebasan 60. Karena t-hitung > t-tabel, disimpulkan bahwa koefisiensi jalur X1 terhadap X2 adalah signifikan. Dengan demikian, kepemimpinan dosen dapat ditingkatkan melalui komitmen organisasi dan budaya mikro kampus sehingga para dosen dapat terus meningkatkan kinerja mereka. Kata kunci: komitmen organisasi, budaya mikro, dan kepemimpinan